Indian English writing : a critical evaluation - All India English Teachers' Conference 2001 : Government Hamidia College); Gautam, G. S. (Gyan Singh), 1958-; Saxena, M. C. (Professor of English) (New Delhi : Classical Pub., 2012)
Papers presented at the 45th All India English Teachers' Conference, held at Bhopal in 2001
Includes bibliographical references
Keywords: Indic literature (English) -- History and criticism -- Congresses